EfrAB, an ABC Multidrug Efflux Pump in Enterococcus faecalis - Lee, Eun-Woo (American Society for Microbiology, 2003)
A DNA fragment responsible for resistance to antimicrobial agents was cloned from the chromosomal DNA of Enterococcus faecalis ATCC 29212 by using drug-hypersensitive mutant Escherichia coli KAM32 as a host cell. Cells of E. coli KAM32 harboring a recombinant plasmid (pAEF82) carrying the DNA fragment became resistant to many structurally unrelated antimicrobial agents, such as norfloxacin, ciprofloxacin, doxycycline, acriflavine, 4′,6-diamidino-2-phenylindole, tetraphenylphosphonium chloride, daunorubicin, and doxorubicin. Since the sequence of the whole genome of E. faecalis is known, we sequenced several portions of the DNA insert in plasmid pAEF82 and identified two open reading frames within the insert. We designated the genes efrA and efrB. A search of the deduced amino acid sequences of EfrA and EfrB revealed that they are similar to each other and that they belong to the ATP-binding cassette (ABC) family of multidrug efflux transporters. Transformed E. coli KAM32 cells harboring efrAB showed energy-dependent efflux of acriflavine. The efflux activity was inhibited by reserpine, verapamil, and sodium-o-vanadate, known inhibitors of ABC efflux pumps.